Anti diabetic (AD) studies of picolinium maleate nano crystals. (2020) - Senthil Kannan, K.; Gayathri Devi, S.; Nagarajan, Prithiviraj; Flora, G.; Ranadevan, R.
Abstract: By and large in material applications nano materials and nano crystals are broadly utilized and numerous use in all fields of science and innovation and they have some extraordinary properties. Right now changed over large scale precious stone into nano crystal by ball milling strategy, Crystals are investigated by SXRD technique for parameters. For large scale precious crystals single XRD are utilized, for nano powder XRD are utilized and the crystal is changed over into nano crystal which are utilized for channel applications and against diabetic investigation of the nano. PM nano Crystal hindrance esteems are expanded with legitimate increment in the estimation of fixation, IC50 values are 20.2 for nano crystal of PM and 20.26 at large scale level